The Meaning of “Clean” in Anti-doping Education and Decision Making: Moving Toward Integrity and Conceptual Clarity - Petróczi, Andrea; Boardley, Ian D. (Frontiers in Sports and Active Living, 2022)
With the World Anti-Doping Agency’s International Standard for Education (ISE) coming into effect in 2021, the clean-sport movement is at a pivotal stage. Through this conceptual paper we juxtapose the sector-wide anti-doping education as set out in the ISE on the decision-making process at the individual level. We discuss three critical issues for the clean-sport movement. First, we make the case for doping being a ‘wicked’ problem and outline the possible implications of this for prevention and detection. Second, we consider why we need to address regulative, normative, and cognitive components of clean sport if we are to maximise its legitimacy. Third, we critically expose the fluidity with which clean sport is defined, and the implications of defining clean sport in substance- versus rule-based terms, which respectively lead to theorising clean sport as ‘drug-free’ vs. ‘cheating-free’ sport. Finally, we consider the role and key components of anti-doping education and how the relevance of certain components may be dependent on the way clean sport is defined. Conceptualising doping as a sport integrity issue, we move away from the archaic and delimiting view of clean sport as drug-free sport and conclude with recommendations on how to reconcile values-based education, awareness raising, information provision and anti-doping education within the broader scope of integrity, to support informed decision making and personal agency.